(untitled) (Causa: Jurnal Hukum dan Kewarganegaraan, 2025)
In the revision of Law No. 34 of 2004 concerning the Indonesian National Armed Forces (TNI), the prohibition on business for military personnel is discussed in this study. This was a debate in society and in the DPR forum because some wanted to ease this prohibition. However, after the revision process, the regulation still prohibits active soldiers from participating in business. On the other hand, there are concerns that the professionalism and neutrality of the TNI could be affected by involvement in business. The legal analysis and literature research methods are used in this study to see how the regulation on the prohibition on business for active soldiers has developed, from the old regulation to the changes made in the latest revision of the TNI Law. This study also discusses the arguments underlying the proposal to liberalize the prohibition on business as well as the arguments of those who want to maintain it. The results of the study show that despite efforts to relax the regulation, the revision of the TNI Law still prohibits active soldiers from doing business. This is done to ensure that the TNI remains neutral, professional, and is seen as a state institution that should not be involved in conflicts of interest. This study finds that this prohibition is very important for strengthening democratic governance and maintaining public trust in the military. Dalam revisi Undang-Undang TNI 34 Tahun 2004 tentang Tentara Nasional Indonesia (TNI), larangan bisnis bagi anggota militer dibahas dalam penelitian ini. Sempat menjadi perdebatan di masyarakat dan di forum DPR karena ada yang ingin mempermudah larangan ini. Namun, setelah proses revisi, aturan tetap melarang prajurit aktif untuk berpartisipasi dalam bisnis. Sebaliknya, ada kekhawatiran bahwa profesionalisme dan netralitas TNI dapat terpengaruh oleh keterlibatan dalam bisnis. Metode analisis hukum dan penelitian literatur digunakan dalam penelitian ini untuk melihat bagaimana aturan larangan bisnis bagi prajurit aktif ini berkembang, mulai dari aturan lama hingga perubahan yang dibuat dalam revisi UU TNI yang terbaru. Penelitian ini juga membahas argumen yang mendasari usulan liberalisasi larangan bisnis serta argumen pihak yang ingin mempertahankannya. Hasil penelitian menunjukkan bahwa meskipun ada upaya untuk melonggarkan aturan, revisi UU TNI tetap melarang para prajurit aktif berbisnis. Ini dilakukan untuk memastikan TNI tetap netral, profesional, dan dipandang sebagai institusi negara yang tidak boleh terlibat dalam konflik kepentingan. Studi ini menemukan bahwa larangan ini sangat penting untuk memperkuat pemerintahan demokratis dan menjaga kepercayaan masyarakat terhadap militer.